2013
DOI: 10.3724/sp.j.1005.2013.01217
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and functional analysis of Phyllostachys edulis MYB transcription factor PeMYB2

Abstract: MYB-type transcription factor is one of the largest families in plants, which plays important roles in accepting stress signals from environment and regulating the expression of stress-tolerant genes. In this paper, using homologous cloning and RACE technology, a MYB-type transcription factor, designated PeMYB2, was cloned from Phyllostachys edulis. The results of bioinformatics showed that PeMYB2 is a typical R2R3-MYB. It contained two tandem repeats in its N-terminus, and a membrane protein DUF3651 in its C-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Increasing amounts of research has indicated that MYB proteins play fundamental roles in the regulation of gene expression in response to environmental change, where they act as active players in abiotic stress signaling ( Ambawat et al, 2013 ; Li et al, 2015 ). In moso bamboo, the overexpression of PeMYB2 (named PheMYB2R-73 in our study) could strengthen the tolerance of the transgenic Arabidopsis lines under salt stress conditions ( Xiao et al, 2013 ). Moreover, “the MYB TFs might play crucial roles in regulating, acclimating, and modulating gene expression in photosynthetic processes in response to the high-light stress of moso bamboo” ( Zhao et al, 2016 ).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Increasing amounts of research has indicated that MYB proteins play fundamental roles in the regulation of gene expression in response to environmental change, where they act as active players in abiotic stress signaling ( Ambawat et al, 2013 ; Li et al, 2015 ). In moso bamboo, the overexpression of PeMYB2 (named PheMYB2R-73 in our study) could strengthen the tolerance of the transgenic Arabidopsis lines under salt stress conditions ( Xiao et al, 2013 ). Moreover, “the MYB TFs might play crucial roles in regulating, acclimating, and modulating gene expression in photosynthetic processes in response to the high-light stress of moso bamboo” ( Zhao et al, 2016 ).…”
Section: Discussionmentioning
confidence: 80%
“…Moreover, they might be involved in drought-responsive and gibberellic acid (GA)-signaling pathways to improve stress resistance and further activate downstream genes to influence flowering transition ( Gao et al, 2014 ). Although many studies have emphasized the importance of MYB proteins and have facilitate a preliminary understanding of this large gene family, with the exception of PeMYB2 ( Xiao et al, 2013 ), few members of moso bamboo MYB genes have been well functional characterized, particularly in comparison with model plants. There is thus an urgent need to characterize the roles of MYB s in moso bamboo and to further our understanding of these genes.…”
Section: Introductionmentioning
confidence: 99%